المصاحف الرسمية المطبوعة في بلاد المغرب العربي - قديري, مختـار بن حسين (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2019)
ملخص هذه الرسالة بعنوان: "نسخ مصحف رسمية مطبوعة باللغة البلدان المغاربية ، دراسة تقويمية حسب ال قواعد علوم القراءة "وكان الجواب على مشكلتها الرئيسية كما يلي التالي: السؤال الرئيسي الذي يطرح أمام الباحث هو: إلى إلى أي مدى كانت النسخ الرسمية المطبوعة من القرآن في المغرب العربي توافق الدول على قواعد علوم القراءة والنسخ القديمة من المصحف الذي كتبه الصحابة رضي الله عنه ترضى عنهم) والذين نسخوا؟ ما هو التأثير من هذه التناقضات ، إن وجدت ، على الناس الذين يقرؤون اليوم؟ تم تقسيم هذه الأطروحة إلى أربعة فصول: تم تكريس الأول إلى تعريف المصاحف الرسمية المطبوعة في المصحف دول المغرب العربي والثاني والثالث للتقييم دراسة هذه المصاحف وفق قواعد العلوم والتي تتعلق بكتابة القرآن وكلماته (القرآن كتابة ، حروف متحركة ، تجزئة ، رواية ، عد ، القرآن وقفة ، أسماء السور) ، وفي الفصل الأخير ركزت على أكثر من غيرها الجوانب الفنية الهامة للمصاحف المصاحف المغاربية بلدان. أهم النتائج هي: التوافق الكبير لـ نسخ المصحف في دول المغرب العربي مع قواعد القراءة العلوم (كتابة القرآن ، الحروف المتحركة ، التجزئة ، الرواية ، العد ، وقفة القرآن ، وأسماء السور). على الرغم من أن هذه العلوم هم الاجتهاد ، واضطرابهم له تأثير كبير في السيطرة على الرواية المعتمدة. وأخيرا أشرت إلى بعض التوصيات أهمها ومنها: الدعوة لتأسيس مجموعة مغربية لطباعة المصحف الشريف ، وتوحيد المصاحف المصاحف الدول المغاربية واقامة الندوات والمنتديات التي تهدف لخدمة القرآن الكريم.Summary This thesis is entitled: "Official Printed Copies of the Koran in the Maghreb Countries, an Evaluation Study According to the Rules of Reading Sciences". The answer to its main problem was as follows: The main question that arises in front of the researcher is: To what extent do the official printed copies of the Koran in the Maghreb countries agree to the rules of reading sciences and the old copies of the Koran which have been written by the Companions (may Allaah be pleased with them) and the ones which copied? What is the impact of these contradictions, if any, on people reading today? This thesis was divided into four chapters: the first was devoted to the definition of the official printed copies of the Koran in the Maghreb countries, and the second and third ones for the evaluation study of these copies of the Koran according to the rules of sciences which related to the writing of the Koran and its words (Koran writing, vowelization, fractionation, narrating, counting, the Koran’s pause, Surahs’ names), and in the final chapter, I focused on the most important technical aspects of the Koran copies of the Maghreb countries. The most important findings are: the great compatibility of the copies of the Koran in the Maghreb countries with the rules of reading sciences (Koran writing, vowelization, fractionation, narrating, counting, the Koran’s pause, Surahs’ names). Although these sciences are diligence, their disorder has a significant impact in the control of the narrating adopted. Finally, I referred to some recommendations, the most important of which are: the call for the establishment of a Moroccan collection to print the Holy Koran, the unification of the Koran copies of the Maghreb countries, and the establishment of seminars and forums which aims to serve the Holy Koran.
دراسة تقييمية وفق قواعد علوم القراءات
أطروحة دكتوراه تخصص : التفسيروالتشريع املقارن فرع: التفسيروعلوم القرآن في العلوم الاسلامية
Keywords: the Koran- Official Printed Copies - Maghreb Countries- the Rules of Reading Sciences; القرآن- النسخ الرسمية المطبوعة- دول المغرب العربي- قواعد علوم القراءة